A case report of malignant hypertension and multiorgan dysfunction during immunotherapy for gallbladder cancer - Anthon, Caroline; Pierret, Hugo; Houssiau, Frederic; Aydin, Selda; De Cuyper, Astrid; Van Marcke, Cédric; Van Den Eynde, Marc; Mazzeo, Filomena; Cornelis, Frank; Galot, Rachel; Duhoux, Francois P.; Baurain, Jean-François; et al. (Frontiers in Oncology, 2025)
We report the case of a 77-year-old woman with metastatic gallbladder cancer who initially received adjuvant capecitabine following surgery. During this period, she developed a facial rash, associated with a positive antinuclear antibody (ANA) with a titer of 1:320. Six months later, disease recurrence prompted treatment with gemcitabine, cisplatin, and durvalumab. Shortly after completing six cycles of chemo-immunotherapy, she presented with rapidly progressive dyspnea, severe hypertension, thrombotic microangiopathy (TMA; confirmed on renal pathology), and multiorgan dysfunction, including hepatic and muscular involvement. Laboratory workup revealed a strongly positive ANA titer (1:1280) corresponding to strongly positive anti-Th/To antibodies. Although the clinical presentation was highly suggestive of scleroderma renal crisis (SRC), it remained challenging to determine whether this was an immune-related adverse event, a paraneoplastic manifestation, or an exacerbation of a pre-existing autoimmune condition. This case illustrates the diagnostic and therapeutic complexity of autoimmune phenomena in oncology and highlights the importance of thorough autoimmune screening and multidisciplinary collaboration before and during immunotherapy.